A103: Childhood Onset Takayasu Arteritis—Experience From a Tertiary Care Centre in South India. Issue 11 (March 2014) - Kumar, Sathish; Goel, Ruchika; Danda, Debashish; Surin, Ajith Kumar; Bacon, Paul A
Abstract : Background/Purpose: Takayasu Arteritis (TA) is a chronic granulomatous vasculitis of autoimmune etiology characterized by narrowing of aorta and its main branches. It is one of the rarest diseases but the third common cause of vasculitis in pediatric age group. Mortality in juvenile onset TA has been reported to range from 8% to 35%. The outcome of disease has improved recently with interdisciplinary treatment including immunosuppressants and cardiovascular interventional procedures. We aimed to study the clinical features, angiographic findings and outcome of children with TA referred to a single centre in South India over a 9 year period. Methods: Records of TA patients, with symptom onset prior to 16 years of age were studied. Disease Extent Index‐Takayasu (DEI.TAK), Indian Takayasu Arteritis Score 2010, and Takayasu Arteritis Damage Score (TADS) were calculated retrospectively using clinical information in electronic records. Cumulative incidence of sustained remission was estimated using Kaplan Meir curve Results: Forty patients with childhood onset TA with median age of onset of 12.5 (range 1–16) years presented at a median diagnostic delay of 11.3 (range 1–60) months. Commonest presenting features were hypertension, headache, malaise and fever. Pulse‐less disease was observed in 25 (62.5%) cases. Majority (n = 28) had active disease with raised inflammatory markers, high baseline DEI.TAK score of 10 (3–24) and high median TADS of 7 (3–14). Of the 34 patients, followed up for 21.5 (range 3–192) months, remission was attained in 30, however cumulative sustained remission was achieved in only 29% of them at 5 years. Median period of sustained remission was 22.5 months (95% CI 17.1–26.8). New areas of vessel involvement were observed in 13 patients. Disease progression was arrested in majority (n= 20) with aggressive medical management and endovascular intervention. All 11 patients with an increment in TADS of ≥4 units during follow up had persistently active or relapsing disease. There was single case with fatality. Conclusion: Corticosteroids and immunosuppressive therapy were effective in the control of disease activity. Progression of damage was associated with persistent inflammation. Continued surveillance by clinical instruments and imaging is warranted.